Medium-sized mammals in peri-urban environments in southern Brazil - Carla Denise Tedesco; Douglas Machado da Silva; Noeli Zanella (Acta Scientiarum. Biological Sciences, 2018)
Anthropic effects on natural environments caused by urban expansion or agriculture have been identified as one of the causes for the decline in species richness. In southern Brazil, the urbanization process affects the local fauna and reduces the diversity of mammalian species. This study was conducted from 2012 to 2015 with the objective of gathering information on mammalian species in a peri-urban area. Data was collected four consecutive days each month for 42 months using sand plots and visual searches. Occasional encounters and camera traps complemented were used to complement the data. We recorded 15 mammal species belonging to 10 families. The species with the highest abundance, taking into account all the applied methods, were Didelphis albiventris, Mazama gouazoubira and Cerdocyon thous. Four species were listed as endangered (Puma yagouaroundi, Leopardus guttulus, Nasua nasua, and Dasyprocta azarae).